SIGNIFICANCE OF DETERMINATION OF LIPOPROTEIN-ASSOCIATED PHOSPHOLIPASE A2 IN PATIENTS WITH ANTIPHOSPHOLIPID SYNDROME - Lević, Marija (Medicinski podmladak, 2024)
Introduction: Lipoprotein-associated Phospholipase A2 (LP-PLA2) is an essential mediator of inflammation, which has a vital role in inflammatory diseases of the vascular system. It has a significant role in the occurrence of thrombosis, the main manifestation of antiphospholipid syndrome. The Aim: To investigate the values of Lp-PLA2 in patients with antiphospholipid syndrome (APS) regarding the distribution of all data, age, gender, disease duration, and type of disease. Material and Methods: This experimental work analysed samples of 74 patients diagnosed with APS. Concentrations of Lp-PLA2 were determined by ELISA (Enzyme-Linked Immunosorbent Assay) method. Results: The activity of Lp-PLA2 was higher than recommended referent values. There is no significant difference in the values of Lp-PLA2 concerning patientsʼ age, gender, disease duration, and type of the disease (P > 0,05). There was a statistically significant correlation between the patientsʼ age and the disease duration (rho = 0,359; P = 0,002). Conclusion: Elevated values of Lp-PLA2, so as the correlation between the years of age and duration of APS can be important information to doctors in the appropriate management of these patients. It is up to future prospective studies to confirm the significance of Lp-PLA2 determination in patients with APS.